Exercise training prevents increased intraocular pressure and sympathetic vascular modulation in an experimental model of metabolic syndrome - Castro,E.F.S. (2015)
The present study aimed to study the effects of exercise training (ET) performed by rats on a 10-week high-fructose diet on metabolic, hemodynamic, and autonomic changes, as well as intraocular pressure (IOP). Male Wistar rats receiving fructose overload in drinking water (100 g/L) were concomitantly trained on a treadmill for 10 weeks (FT group) or kept sedentary (F group), and a control group (C) was kept in normal laboratory conditions. The metabolic evaluation comprised the Lee index, glycemia, and insulin tolerance test (KITT). Arterial pressure (AP) was measured directly, and systolic AP variability was performed to determine peripheral autonomic modulation. ET attenuated impaired metabolic parameters, AP, IOP, and ocular perfusion pressure (OPP) induced by fructose overload (FT vs F). The increase in peripheral sympathetic modulation in F rats, demonstrated by systolic AP variance and low frequency (LF) band (F: 37±2, 6.6±0.3 vs C: 26±3, 3.6±0.5 mmHg2), was prevented by ET (FT: 29±3, 3.4±0.7 mmHg2). Positive correlations were found between the LF band and right IOP (r=0.57, P=0.01) and left IOP (r=0.64, P=0.003). Negative correlations were noted between KITT values and right IOP (r=-0.55, P=0.01) and left IOP (r=-0.62, P=0.005). ET in rats effectively prevented metabolic abnormalities and AP and IOP increases promoted by a high-fructose diet. In addition, ocular benefits triggered by exercise training were associated with peripheral autonomic improvement.